Patient-made axillary crutches enabled home-based rehabilitation: A case report - Chakrabarty, Shohag; Ashikul Islam; Abu Taslim (Bangabandhu Sheikh Mujib Medical University Journal, 2025)
Background: Pelvic fractures substantially impair mobility and functional recovery, particularly in low- and middle-income countries where access to rehabilitation services and assistive devices is limited. This report highlights the role of patient-led innovation at the patient’s home in addressing such constraints. Case description and management: A 68-year-old physically active man from rural Bangladesh sustained a stable pelvic fracture following a fall. He was managed non-surgically. Due to the unavailability of standard mobility aids and financial constraints, the patient himself designed and constructed an axillary crutch using locally sourced bamboo and wood. A physiatrist trained him on safe crutch use and proper gait through in-person visits and telemedicine. Iterative functional trials informed device modifications to ensure appropriate fit, reduce axillary pressure, and support an effective three-point gait. Follow-up at 6, 9, and 12 weeks post-discharge demonstrated progressive improvement in mobility and pain control. The Functional Independence Measure score improved from 115 at baseline to 123 at final follow-up. Conclusions: This case demonstrates that with proper guidance and motivation, patient-driven, low-cost assistive technologies can be a viable means of functional recovery in resource-limited settings. This example of patient-led assistive device development and its use may assist people who work in community-based rehabilitation.